المواطنة وأبعاد التعايش والتمكين: دراسة دستورية في منهجية التطبيق: CITIZENSHIP AND THE DIMENSIONS FOR CO-EXISTENCE AND EMPOWERMENT: A CONSTITUTIONAL STUDY IN THE APPLICATION METHODOLOGY (International Seminar on Syariah and Law (INSLA), 2020)
the study aims to clarify the dimensions of peaceful coexistence and empowerment of single multiple societies in its ethnicities and religions under the Islamic constitutional system, through extrapolation of some prophetic texts and agreements, the most prominent of which is the famous Medina Agreement, which focused on highlighting the importance of belonging to the homeland in light of the plurality of different ethnicities and religions, Nevertheless, diversity was not a cause of societal schizophrenia, disagreement, rivalry, and quarrels. Rather, constitutional and methodological systems have emerged that regulate relations between groups of a single community that are diverse in their religions and ethnicities, through the constitutional statement contained in the Prophet's City Agreement, which stipulated some of its provisions On basic issues of citizenship, as well as other provisions regulating relations between the groups of the diverse society with its religions and ethnicities, this diversity included three groups in the first prophetic civil society, namely the Muslim supporters, the immigrant Muslims, and the Jews, and it was the supreme goal of the constitutional statement in the Convention Medina is an illustration that Medina is one country of different ethnicities and religions, for which they cannot manage, develop, develop and defend E, except through those constitutional systems that regulated citizenship and relations between the groups of a single, diverse, plural society. تهدف الدراسة إلى بيان أبعاد التعايش السلمي والتمكين للمجتمع الواحد المتعدد في عرقياته ودياناته في ظل النظام الدستوري الإسلامي، وذلك من خلال استقراء بعض النصوص والاتفاقيات النبوية والتي من أبرزها صحيفة المدينة المنورة، والتي ركزت على إبراز أهمية الانتماء للوطن في ظل تعدد للعرقيات والديانات المختلفة، ومع ذلك، فإن ذلك التنوع لم يكن سببًا من أسباب الانفصام المجتمعي والخلاف والتناحر والتشاجر، وإنما برزت بشكل واضح نظم دستورية ومنهجية تنظم العلاقات بين فئات المجتمع الواحد والمتنوعة في دياناتها وعرقياتها، من خلال البيان الدستوري الذي حوته صحيفة المينة النبوية والتي نصت في بعض بنودها على أمور أساسية في المواطنة، كما نصت أيضا بنود أخرى تنظم العلاقات بين فئات المجتمع المتنوع بدياناته وعرقياته، وقد ضم هذا التنوع ثلاث فئات في المجتمع المدني النبوي الأول، وكانت نلك الفئات هم المسلمون الأنصار والمسلمون المهاجرون، واليهود، وقد كان الهدف الأسمى من البيان الدستوري في صحيفة المدينة هو إيضاح أن المدينة المنورة بلد واحد لعرقيات وديانات مختلفة، لا يمكن لهم التمكن من إدارته وتطويره تنميته والدفاع عنه إلا من خلال تلك النظم الدستورية التي نظمت المواطنة والعلاقات بين فئات المجتمع المتعدد المتنوع الواحد.